Interplay of shared leadership practices of principals, teachers’soft skills and learners’competitiveness in covid 19 era: implications to economics of educational leadership - Alanya Beltran, Joel Elvys (2021)
The COVID 19 pandemic had a significant impact on both the administration and instructional delivery. A close partnership between administrators and teachers is essential to students' overall growth, particularly in this COVID 19 era. This study employed a descriptive correlational research design. A survey was done using online to selected schools in South East Asian countries. From the study, it can be inferred that the highly positive results are seen on the level of principal shared leadership practices are manifested by the school heads, teachers' soft skills enhancement, and learners' competitiveness. The school heads are capable of exuding shared leadership aspects on effective communication, proper coordination, direction, and influence. Test of relationship showed a positive interplay between principals' shared leadership with the selected variables on teachers' soft skills and learners' competitiveness. Research on the comparative impacts of leadership styles will assist policymakers and practitioners in better understand which leadership techniques are most successful for specific elements of school reform efforts, in our view. Further, the implications of this study will help teachers better their interpersonal and administrative abilities while administrators are urged to continue to improve their leadership techniques. The result of this present study will provide a way for policymakers and other stakeholders to fund allocation and develop a plan of action to strengthen principal leadership in the COVID 19 era.